TRADISI BUDAYA TORAJA DAN DOGMA KRISTEN: STUDI KASUS MA'PAKANDE DEWATA - Santini Sa'dan; Datu Masiri Allobunga'; Sari allo; Dewi Dalle; Sidar (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This research explores the complex dynamics between Toraja cultural traditions and Christian dogma, focusing on the Ma'pakande Dewata ritual, an ancestral offering practice rooted in the Aluk Todolo belief system. Since the arrival of Christianity in the early 20th century, the Toraja people have faced an identity dilemma between preserving their cultural heritage and accommodating the teachings of their newly adopted religion. This study employs a qualitative approach with an ethnographic case study design involving  informants, consisting of to minaa (traditional spiritual leaders), pastors, customary leaders, and Toraja Christian families. Data were collected through participant observation, in-depth interviews, document studies, and focus group discussions, then analyzed using thematic analysis methods. The findings reveal that the tension between Ma'pakande Dewata and Christian dogma reflects a fundamental conflict between animistic-communalistic and monotheistic-individualistic worldviews. Toraja Christians have developed four main adaptation strategies: total assimilation, pragmatic syncretism, creative inculturation, and strategic selectivity. The choice of strategy is influenced by factors such as church denominational affiliation, position in the customary structure, education level, family cohesion, and personal experience. This research contributes to the understanding of religious syncretism and inculturation in indigenous community contexts, and provides recommendations for developing more culturally sensitive contextual theology and cultural heritage preservation policies that respect the religious dimensions of society.